Musical warriors: British military music and musicians during the French Revolutionary and Napoleonic Wars - O'Keeffe, EW (2022)
Military music was pervasive in Britain and Ireland during the French Wars but has received limited attention from historians. This thesis interprets martial music-making as a core military activity and an integral part of wider musical culture. A critical tool of communication and discipline, music sounded the alarm, aided recruitment, and governed soldiers’ routines and bodily movements. Officers invested heavily in military bands, regarding them as social amenities, sources of prestige, and essential for maintaining soldiers’ morale. Regiments competed and cooperated in a seller’s market for musical labour, engaging knowledgeable civilian performers and training a mass of novice instrumentalists through a cogent instructional programme.